2010
DOI: 10.1590/s0034-737x2010000100008
|View full text |Cite
|
Sign up to set email alerts
|

Influência da capacidade de campo na taxa de crescimento do cafeeiro conilon

Abstract: Influence of field capacity on the growth rate of Conilon coffeeThe objective of this work was to evaluate the influence of field capacity (FC) on the growth rate of the conilon coffee plant by using three tensions (0.006 MPa (FC 1 ), 0.010 MPa (FC 2 ) and 0.033 MPa (FC 3 )) in two soils (Red-Yellow Oxisol and Red-Yellow Ultisol). The experiment was carried out in a greenhouse at the Center of Studies and Technology Dissemination in Forestry, Water Resources and Sustainable Agriculture, in the municipality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
4
0
6
Order By: Relevance
“…Soares et al (2011) found similar results for tomato cultivation; so drought in the vegetative and reproductive phase provides lower height of plants, number of leaves and stem diameter. Analyzing the development of the coffee conilon it was found that drought reduced the stem diameter of this species (Dardengo et al, 2009). In rosemary-pepper cultivated at different irrigation levels, Alvarenga et al (2012) and Figueiredo et al (2009) observed better growth occurring with greater water availability.…”
Section: Resultsmentioning
confidence: 95%
“…Soares et al (2011) found similar results for tomato cultivation; so drought in the vegetative and reproductive phase provides lower height of plants, number of leaves and stem diameter. Analyzing the development of the coffee conilon it was found that drought reduced the stem diameter of this species (Dardengo et al, 2009). In rosemary-pepper cultivated at different irrigation levels, Alvarenga et al (2012) and Figueiredo et al (2009) observed better growth occurring with greater water availability.…”
Section: Resultsmentioning
confidence: 95%
“…As for the higher values obtained by FCIPvg, we emphasize the importance of future comparisons with results determined in field, to confirm whether there is an overestimation or if the estimate is accurate. In experiments of irrigation management in Oxisols, higher values of water content corresponding to field capacity were chosen, as in the case of Dardengo et al (2010), who found an increased growth rate in coffee when, for irrigation management, the moisture at field capacity was estimated at 10 kPa compared with 33 kPa in a Red-Yellow Latosol, i.e., 33 kPa underestimated the upper limit of soil water availability for coffee for those conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Dardengo et al (2009) report that decreases in growth rates in this period may also be associated with prolonged drought (43 days of drought occurred between 01/15 and 02/27, a period during which only one 25-mm irrigation could be performed). It is also noteworthy that conilon coffee plants show metabolic losses due to drought and also respond differently to soil water deficit (DaMatta et al, 2003;Pinheiro et al, 2004;Praxedes et al, 2006).…”
Section: Resultsmentioning
confidence: 99%